Comparison of methods to estimate missing rainfall data for short term period at UMP Gambang - A. A. G., Nadiatul Adilah; H., Hannani (IOP Publishing Ltd, 2021)
Hydrological analysis is crucial for planning or designing engineering structures and water resources system as stated by World Meteorological Organization (WMO). A long and complete data set of rainfall is required in order to carry out the hydrological study successfully. However, the most common problem that always come up in data collection is the lacking of data due to some occurrence involving the equipment installed that may cause the error to occur. For this study, another problem that has been a concern is the availability of the rainfall data is insufficient as the studied area is newly developed so the limitation of the existing data may affect to the relevance of this study. Therefore, this study is mainly conducted to compare three existing methods from previous scholars which are Arithmetic Mean Method, Normal Ratio Method and Inverse Distance Weighting Method to prove whether these methods are capable to fill the gaps of rainfall data for short term period of study. The existing data collected at the target station are then compared with the three methods whether the results gained are similar or otherwise. Analysis shows that the study for short term period is irrelevant due to the insufficiency of data collection.